2018
DOI: 10.1093/protein/gzy034
|View full text |Cite
|
Sign up to set email alerts
|

A single mutation in cyclodextrin glycosyltransferase from Paenibacillus barengoltzii changes cyclodextrin and maltooligosaccharides production

Abstract: Cyclodextrin glycosyltransferases (CGTases) are bacterial enzymes that catalyze starch conversion into cyclodextrins, which have several biotechnological applications including solubilization of hydrophobic compounds, masking of unpleasant odors and flavors in pharmaceutical preparations, and removal of cholesterol from food. Additionally, CGTases produce maltooligosaccharides, which are linear molecules with potential benefits for human health. Current research efforts are concentrated in the development of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Analysis of the microenvironments showed that the hydrophobicity around these two positions was significantly increased after the mutations (Figure 7B−D), which may reduce the diffusion of water in the active site and thus boost transglycosylation reaction. 8,31,34,38,39 Interestingly, C510 and H512 are located at the end of a cleft leading to the active site and look like a pair of gatekeepers (Figure 7B). Previous studies have shown that water channels can be formed based on such architectures, in which water molecules could be transferred from the protein surface to the active site.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the microenvironments showed that the hydrophobicity around these two positions was significantly increased after the mutations (Figure 7B−D), which may reduce the diffusion of water in the active site and thus boost transglycosylation reaction. 8,31,34,38,39 Interestingly, C510 and H512 are located at the end of a cleft leading to the active site and look like a pair of gatekeepers (Figure 7B). Previous studies have shown that water channels can be formed based on such architectures, in which water molecules could be transferred from the protein surface to the active site.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This indicated that the mutations caused very little perturbation to the overall structure and affected the enzymatic property through subtle molecular adjustments. Analysis of the microenvironments showed that the hydrophobicity around these two positions was significantly increased after the mutations (Figure B–D), which may reduce the diffusion of water in the active site and thus boost transglycosylation reaction. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…Paenibacillus spp. (Castillo et al, 2018). CGTase can catalyse four reactions: cyclization, coupling, disproportionation, and hydrolysis (Li et al, 2014b), though the hydrolysis activity is relatively weak (Costa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, γ-CGTase with improved thermostability successfully increased yields of γ-CD and total CDs. In others work, protein engineering for improving yield of CDs payed more attention on changing product specificity or improving cyclization activity (Castillo et al, 2018;Lee et al, 2002;Wang et al, 2020). There also had limited studies to increase the yield of CDs by improving the thermostability.…”
Section: Ca 2+ and Site-directed Mutagenesis In Combination Help To I...mentioning
confidence: 99%